Analisis Determinan Terhadap Kepatuhan Wajib Pajak Orang Pribadi - ilham ramadhan Nasution (CERED Indonesia Institute, 2021)
The purpose of this study was to determine the effect of tax service quality, understanding of tax regulations and tax sanctions partially and simultaneously on individual taxpayer compliance at the Medan Belawan Pratama Tax Service Office. The population in this study were all individual taxpayers registered at the Medan Belawan Pratama Tax Service Office as many as 78,182. The research was conducted in 2018. The data analysis technique used in this research is descriptive statistics, namely by describing and describing the data collected using Validity Test, Reliability Test, Normality Test, Multicollinearity Test, Heteroscedasticity Test, Multiple Linear Regression Analysis, Correlation Coefficient and determination, Partial Test and Simultaneous Test. The results of this study indicate that the Quality of Tax Services, Understanding of Tax Regulations and Tax Sanctions at the Medan Belawan Pratama Tax Service Office partially have a significant effect on individual taxpayer compliance